Wheat Biofortification: Utilizing Natural Genetic Diversity, Genome-Wide Association Mapping, Genomic Selection, and Genome Editing Technologies - Gupta, Om Prakash; Singh, Amit Kumar; Singh, Archana; Singh, Gyanendra Pratap; Bansal, Kailash C.; Datta, Swapan K. (Frontiers in Nutrition, 2022)
Alleviating micronutrients associated problem of hidden hunger to safeguard optimum health conditions in children below five years and women of childbearing age, especially in resource-poor nations, remains a significant challenge. One of the most important staple food crops, wheat attracts the highest global research priority for micronutrients (Fe, Zn, and Se) and protein biofortification. Wild relatives and cultivated species of wheat have witnessed significant natural genetic variability for these micronutrients, which has successfully been utilized to breed micronutrient dense wheat varieties. This has enabled the release of 40 biofortified wheat cultivars for commercial cultivation in different countries, including India, Bangladesh, Pakistan, Bolivia, Mexico and Nepal. In this review, we have systematically analyzed the current understanding of availability and utilization of natural genetic variations for grain micronutrients and proteins among cultivated and wild relatives, QTLs/gene and different genomic regions regulating the accumulation of micronutrients, and the status of micronutrient biofortified wheat varieties released for commercial cultivation across the globe. In addition, we have also discussed the potential implications of emerging technologies such as genome editing to improve the micronutrient content and their bioavailability.